Dilemmas and Pathways in the Construction of Industrial Colleges in Vocational Institutions from the Stakeholder Perspective - Li, Yuqiang (Journal of Advanced Research in Education, 2025)
Industrial colleges have become an increasingly important vehicle for integrating industry and education in vocational education, attracting broad attention from both scholars and society. From the stakeholder perspective, the construction of such colleges involves schools, enterprises, governments, industry associations, teachers, students, enterprise employees, parents, and the public. These factors engage in complex interactions that often generate conflicts and dilemmas. Value divergences, organizational differences, cultural gaps, property-rights ambiguities, and identity recognition issues have all hindered effective collaboration. Addressing these challenges requires balancing diverse values, fostering consensus while respecting differences, establishing robust mechanisms, clarifying property rights, and promoting collaborative synergy to fully realize the role of industrial colleges in advancing industry-education integration.